THE INFLUENCE OF MOTIVATION, SUPERVISION AND LEADER-MEMBER EXCHANGE (LMX) ON EMPLOYEE PERFORMANCE WITH TURNOVER INTENTION AS AN INTERVENING VARIABLE AT PT BANK MESTIKA DHARMA, TBK PEMATANG SIANTAR CITY - Nitalia, Nitalia; Butarbutar, Marisi; Efendi, Efendi (Sekolah Tinggi Ilmu Ekonomi Sultan Agung Pematangsiantar, 2022)
Hasil peneltiian dapat disimpulkan sebagai berikut: 1. Motivasi sudah baik, pengawasan sudah baik, leader member exchange sudah baik, turnover intention sudah rendah dan kinerja karyawan sudah baik. 2. Motivasi, pengawasan, leader member exchange berpengaruh negatif dan signfikan terhadap turnover intention baik secara simultan maupun parsial kemudian turnover intention berpengaruh negatif dan signifikan terhadap kinerja karyawan. 3. Terdapat hubungan antara variabel bebas dimana terdapat hubungan yang rendah antara motivasi dengan pengawasan kemudian terdapat hubungan yang sedang antara pengawasan dengan leader member exchange dan terdapat hubungan yang sedang antara motivasi dengan leader member exchange. Terdapat hubungan antara variabel bebas dan terikat, terdapat hubungan yang kuat antara motivasi dengan turnover intention. Hubungan yang kuat antara pengawasan dengan turnover intention. Hubungan yang kuat antara leader member exchange dengan turnover. Hubungan yang sangat kuat antara motivasi, pengawasan, leader member exchange dengan turnover intention. Hubungan yang sangat kuat antara turnover intention dengan kinerja karyawan. 4. Hasil uji hipotesis H0 ditolak, artinya motivasi, pengawasan dan leader member exchange berpengaruh negatif signfikan terhadap turnover intention baik secara simultan maupun parsial.Â The research results can be summarized as follows: 1. Motivation is good, Supervision is good, leader-member exchange is good, the turnover intention is low and employee performance is good. 2. Motivation, Supervision, leader member exchange have a negative and significant effect on turnover intention both simultaneously and partially then turnover intention has a negative and significant effect on employee performance. 3. There is a relationship between the independent variables with a low relationship between motivation and Supervision, a moderate relationship between Supervision and leader-member exchange, and a moderate relationship between motivation and leader member exchange. There is a relationship between the independent and dependent variables, there is a strong relationship between motivation and turnover intention. There is a strong relationship between supervision and turnover intention. There is a strong relationship between leader member exchange and turnover. There is a strong relationship between motivation, Supervision, leader member exchange and turnover intention. There is a very strong relationship between turnover intention and employee performance. 4. The results of the H0 hypothesis test are rejected, meaning that motivation, Supervision and leader member exchange significantly negatively affect turnover intention simultaneously and partially.